1997
DOI: 10.2527/1997.7561514x
|View full text |Cite
|
Sign up to set email alerts
|

Time course of increased plasma cytokines, cortisol, and urea nitrogen in pigs following intraperitoneal injection of lipopolysaccharide.

Abstract: The emerging view is that reduced feed intake, lean muscle accretion, and growth in immunologically challenged pigs is the result of increased cytokine activity, but this has not been directly tested. To begin addressing this issue, 72 crossbred barrows and gilts (11.55 +/- .19 kg BW) were not fed for 12 h and then injected i.p. with 0, .5, or 5 micrograms/kg of Escherichia coli lipopolysaccharide (LPS). Blood was collected by jugular puncture at 0, 2, 4, 8, 12, and 24 h after injection. Plasma levels of tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
162
5
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(201 citation statements)
references
References 28 publications
32
162
5
2
Order By: Relevance
“…The expression of IL-1α, IL-1β, IL-6 and TNFα mRNAs was obviously upregulated by LPS stimulation in a dose-and time dependent manner (Fig. 2) [16]. This observation was similar to what was noted with human monocytes and porcine epithelial cells stimulated with LPS, which strongly upregulated the secretion of IL-1α, IL-6 and IL-8 [8] in a dose dependent manner [2].…”
supporting
confidence: 74%
“…The expression of IL-1α, IL-1β, IL-6 and TNFα mRNAs was obviously upregulated by LPS stimulation in a dose-and time dependent manner (Fig. 2) [16]. This observation was similar to what was noted with human monocytes and porcine epithelial cells stimulated with LPS, which strongly upregulated the secretion of IL-1α, IL-6 and IL-8 [8] in a dose dependent manner [2].…”
supporting
confidence: 74%
“…The immunological challenge resulted in the poor performance of animals (Benson et al, 1993;Klasing and Korver, 1997;Halloy et al, 2004), which was attributed to the partitioning of nutrients away from growth and toward processes associated with inflammatory immune responses in chickens . Some studies indicated that these changes are attributed to the release of proinflammatory cytokines (Johnson, 1997;Webel et al, 1997;Sijben et al, 2001), including TNF, IL-1 and IL-6. In this study, the first and the second LPS challenges significantly increased the pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…A well-documented system for inducing sickness in laboratory animals is injection of lipopolysaccharide (LPS), a component of the outer membrane of gram-negative bacteria. Treatment of animals with LPS evokes a multitude of symptoms of sickness and elaboration of systemic inflammatory cytokines (Johnson and von Borel, 1994;Warren et al, 1997;Webel et al, 1997;Balaji et al, 2002). LPS is a potent inflammatory mediator and has been used to model bacterial infection experimentally in chickens .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Daiwen et al (2008) observed lower protein retention in pigs challenged intramuscularly with LPS when compared with their pair-fed counterparts receiving a saline solution. Webel et al (1997) reported an increase in plasma urea nitrogen levels in association with increased circulating tumor necrosis factor (TNF) -α and IL-6 in pigs intraperitoneally challenged with LPS. It has also been suggested that protein catabolism during disease or inflammation is emphasized due to an imbalance between the supply of amino acids from endogenous proteolysis and those required for the synthesis of acute phase compounds (Reeds et al, 1994).…”
Section: Metabolic Adjustmentsmentioning
confidence: 99%
“…The second effect of cortisol corresponds to a metabolic effect. Indeed, cortisol is a catabolic hormone, which increases energy and nutrient release due to the stimulation of adipose tissue lipolysis and skeletal muscle proteolysis (Johnson, 1997;Webel et al, 1997). This may contribute to increase nutrient availability for the immune response.…”
Section: Neuroendocrine Adjustmentsmentioning
confidence: 99%